Authenticity is Fiction? Relicts, Narration and Hermeneutics - Jörg van Norden (EXARC Journal)
In many ways, authenticity is everybody’s darling: the historian searches for authentic, historic texts in order to write down history objectively; the readers, naturally, appreciate an authentic description of the past; and museum visitors want to see authentic originals, not replicas (Franz 2011, 335; Meiners 2008, 169; Saupe 2010, 185). However, when relics are integrated in a complete surrounding of houses, animals, family life and artistry represented by adequately dressed people, they can be a real attraction (van Norden 2011b, 67; Schwarz 2010, 234f, 237). Neurology explains why that authenticity is so effective: memory is improved by experiencing something with all your senses and in an emotional way (Duisberg 2008, 96; Faber 2008, 133; Pampel 2011, 56). Visitors who smell the smoke of the fireplace in a Rössener house and touch its rough beams feel as though they have travelled back in time and may feel as though they can see with eyes of Stone Age farmers. Visitors are able to leave the present, which in many ways can be confusing, and enter a new cosy ‘pastness’ (Hochbruck 2008, 45; Faber 2008, 117; Schwarz 2010, 240).